2019
DOI: 10.1038/s41598-019-54937-x
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 Predicts Outcome in Patients with ST-Segment Elevation Infarction Independent from Infarct-related Myocardial Injury

Abstract: Syndecan-1 (sdc1) is a surface protein part of the endothelial glycocalyx (eGC). Soluble sdc1 is derived from shedding and indicates damaged eGC. We assessed the predictive value of plasma sdc1 concentrations for future cardiovascular events in acute reperfused ST-segment elevation myocardial infarction (STEMI) patients. A total of 206 patients admitted for STEMI were included in this study (29% female; age 65 ± 12 years) and followed-up for six months. Plasma samples were obtained post-intervention and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…It is well-established that catecholamines regulate blood pressure [34]. In high concentrations, catecholamines can also directly damage the endothelium most likely by enhancing eGC degradation [35][36][37]. For instance, circulating NE and epinephrine were found significantly correlated with plasma SDC1 in patients with ST elevation myocardial infarction, with the highest levels of epinephrine and SDC1 in patients with shock prior to primary percutaneous coronary intervention [36].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that catecholamines regulate blood pressure [34]. In high concentrations, catecholamines can also directly damage the endothelium most likely by enhancing eGC degradation [35][36][37]. For instance, circulating NE and epinephrine were found significantly correlated with plasma SDC1 in patients with ST elevation myocardial infarction, with the highest levels of epinephrine and SDC1 in patients with shock prior to primary percutaneous coronary intervention [36].…”
Section: Discussionmentioning
confidence: 99%
“…CD138 overexpression is beneficial in post‐myocardial infarction in rats since it plays a role in the interaction leukocytes/endothelium 162 . However, elevated soluble CD138 serum level in acute reperfused ST‐segment elevation myocardial infarction patients and patients in cardiogenic shock is associated with increased mortality 163,164 . Thus, these receptors provide new biological roles for IL‐34 and could explain the differences with CSF‐1.…”
Section: Overlapping and Non‐overlapping Functions Of Il‐34 And Csf‐1 In Diseasesmentioning
confidence: 99%
“…A study of plasma syndecan-1 levels (n = 567) demonstrated a positive correlation with all-cause mortality and rehospitalization for heart failure in patients with a preserved ejection fraction [179]. Elevated syndecan-1 levels are also independently associated with increased mortality after ST-elevation MI [180].…”
Section: Neglected Ecm Componentsmentioning
confidence: 99%
“…Syndecan-4 expression in the myocardium is increased in failing hearts (n = 20) compared to non-failing hearts (n = 10). [179,180,182,183] Abbreviations: ACS: acute coronary syndrome; AF: atrial fibrillation; BMI: body mass index; CAD: coronary artery disease; CV: cardiovascular; DCM: dilated cardiomyopathy; EF: ejection fraction; HR: hazard ratio; HF: heart failure; HFpEF: heart failure with preserved ejection fraction; HFrEF: heart failure with reduced ejection fraction; LA: left atrial; LV: left ventricular; LVH: left ventricular hypertrophy; MACE: major adverse cardiac events; MI: myocardial infarction; MMP: matrix metalloproteinase; OPN: osteopontin; PAH: pulmonary arterial hypertension; SLE: systemic lupus erythematosus; SNP: single nucleotide polymorphism; TN-C: tenascin C; TSP: thrombospondin.…”
Section: Syndecansmentioning
confidence: 99%